APPLICATION OF THE SIMULATION METHOD TO IMPROVE ACTIVITY AND OUTCOMES OF INDONESIAN LANGUAGE COURSES AT MIZANUL'ULUM SANROBONE - Rahmatia Maatita; Sitti Rabiah; Nurmia Muin (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The purpose of this study was to describe the increase in the activity and learning outcomes of Indonesian language learning for class X MA of the Mizanul'Ulum Sanrobone Islamic Boarding School through the simulation method. This research is a classroom action research (CAR). The subjects in this study were 12 students in class X at the Mizanul'Ulum Sanrobone Islamic Boarding School. Data collection techniques using test and observation techniques were then analyzed with descriptive qualitative. The results of the study show that the value of student activity and learning outcomes in each cycle continues to obtain different results. After it was done in cycle I, it became more active in learning. Student learning outcomes in the activity of analyzing pre-cycle poetry students who achieved KKM of 0%, in the first cycle of meeting I students who achieved KKM of 25% were in the good category, in the first cycle of meeting II students who achieved KKM of 41.7% were in the category good, in cycle II meeting I students who achieved KKM of 58.5% were in the good category, in cycle II meeting II students who achieved KKM of 16.7% were in the very good category, 66.7% were in the good category. Therefore, it can be concluded that the use of the simulation method can increase student learning activeness in Indonesian subjects.